Molecular Engineering of Metal Complexes for Electrocatalytic Carbon Dioxide Reduction: From Adjustment of Intrinsic Activity to Molecular Immobilization - Yang, Zhi‐Wen; Chen, Jin‐Mei; Qiu, Li‐Qi; Xie, Wen‐Jun; He, Liang‐Nian (Angewandte Chemie International Edition, 2022)
The electrocatalytic CO2 reduction reaction (ECO2RR) is one promising method for storing intermittent clean energy in chemical bonds and producing fuels. Among various kinds of catalysts for ECO2RR, molecular metal complexes with well‐defined structures are convenient for studies of their rational design, structure–reactivity relationships, and mechanisms. In this Review, we summarize the molecular engineering of several N‐based metal complexes including Re/Mn bipyridine compounds and metal macrocycles, concluding with general modification strategies to devise novel molecular catalysts with high intrinsic activity. Through physical adsorption, covalent linking, and formation of a periodic backbone, these active molecules can be heterogenized into immobilized catalysts with more practical prospects. Finally, significant challenges and opportunities based on molecular catalysts are discussed. This Review focuses on molecular catalysts for the electrocatalytic CO2 reduction reaction (ECO2RR) including metal bipyridines and macrocycle complexes, and summarizes the molecular engineering strategies developed to regulate the intrinsic catalytic efficiency and modify the electrode. Guidelines are provided for the rational design of ECO2RR catalytic systems.